A study of factor influencing career choice among final year undergraduate students in UiTM Cawangan Kedah / Nur Aliah Mohd Naziruddin and Mohd Fakhrullah Rosli - Mohd Naziruddin, Nur Aliah; Rosli, Mohd Fakhrullah (2017)
Career choice among students create dilemma to them in choosing the right career for future undertaking. The students need to make career choice either to be employed or self-employed. The career choice decision made by them was influence by various factors. Thus a study about career choice among undergraduate students are carry out to examine the factor that influence career choice made by students. The study will focus at UiTM Cawangan Kedah. The purpose of this study is to examine the relationship between career choice, personality type, occupational knowledge, and social influence. Thru this study, the significant factor able to be identify that influence career choice. A sample of 169 respondents selected using proportionate stratified random sampling. Thru this study, the outcome and result on factor that influence career choice will be used to add up literature in career choice among student especially in local level. In conclusion, this study is important in order to identify the most significant factor that influence career choice.